2009
DOI: 10.1593/neo.09470
|View full text |Cite
|
Sign up to set email alerts
|

Distinct HIC1-SIRT1-p53 Loop Deregulation in Lung Squamous Carcinoma and Adenocarcinoma Patients

Abstract: A HIC1-SIRT1-p53 circular loop in which hypermethylation in cancer 1 (HIC1) represses the transcription of SIRT1 that deacetylates and inactivates p53 thus leading to HIC1 inactivation has been identified in cell and animal models. However, the alteration and prognostic effects of HIC1-SIRT1-p53 circular loop have never been demonstrated in human cancer patients. We examine the HIC1-SIRT1-p53 alterations in 118 lung cancer patients to define their etiological roles in tumorigenesis. We found that patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
74
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 28 publications
4
74
0
Order By: Relevance
“…A previous study reported that patients with SCC had significantly higher low-acetylated p53 status compared with patients with AD (P=0.012), and that low-acetylated p53 was associated with poorer survival relative to that of patients with acetylated p53 (13). These findings indicate that p53 deacetylation may play a role in lung tumorigenesis, particularly for SCC patients.…”
Section: A B C Dmentioning
confidence: 71%
See 4 more Smart Citations
“…A previous study reported that patients with SCC had significantly higher low-acetylated p53 status compared with patients with AD (P=0.012), and that low-acetylated p53 was associated with poorer survival relative to that of patients with acetylated p53 (13). These findings indicate that p53 deacetylation may play a role in lung tumorigenesis, particularly for SCC patients.…”
Section: A B C Dmentioning
confidence: 71%
“…To the best of our knowledge, the current study is the first to report on the association between SIRT1 and HMGA1 expression in lung cancer, although their respective roles in tumorigenesis have been widely studied previously (12)(13)(14)(15)26). HMGA1 proteins are reported to be important in the process of carcinogenesis, based on the HMGA1-p53 interaction.…”
Section: A B C Dmentioning
confidence: 85%
See 3 more Smart Citations